Design and Analysis of Different Optical Attocells Deployment Models for Indoor Visible Light Communication System - Gismalla, Mohammed S.M; Liew Abdullah, Mohammad Faiz; Ahmed, Mustafa Sami; Mabrouk, Wafi A; AL-Fadhali, Najib; Saeid, Elsadig; Supa'at, A.S.M.; Das, B (International Journal of Integrated Engineering, 2021)
Visible light communication (VLC) is a promising candidate that is expected to revolutionize indoor environment communications performance and fulfill fifth generation and beyond (5GB) technologies requirements. It offers high and free bandwidth, electromagnetic interference immunity, low-cost front end and low power consumption. Also, VLC has dual functions that could be utilized in both illumination and communication concurrently. The number of optical attocells (OAs) and their deployment in the room represent the main issue that should be taken into consideration in designing an optimal VLC system. In this paper, we have introduced a new model of five OAs in the typical room. In addition to an investigation of various optical attocells (OAs) deployment models, in which a multi-variable evaluation was performed in terms of received power, illumination, SNR and RMS delay spread in order to determine the optimal OAs model. Also, various modulation schemes performances were investigated which included NRZ-OOK, BPSK, and QPSK in order to improve the BER performance. Results indicated that BPSK modulation had superior BER performance when compared with all OAs models. Further, a comprehensive results analysis and comparison of all proposed models was conducted over various parameters, in which our new proposed OAs model achieved an optimal performance in comparison with the other models.